Pulmonary function in patients with ANCA-associated vasculitis - Dieterich, Johannes; Hellmich, Bernhard; Mahrhold, Juliane; Feng, You-Shan; Rai, Abdallah El; Nessyt, Felix; Specks, Ulrich; Hetzel, Jürgen; Löffler, Christian (Sarcoidosis, vasculitis and diffuse lung diseases, 2024)
Background and aim: Although pulmonary manifestations occur frequently in ANCA-associated vasculitis (AAV), empirical evidence of their impact on pulmonary function is scarce. This study analyzed pulmonary function test (PFT) data from a large cohort of patients with AVV. Results were correlated with findings from diagnostic imaging and disease activity. Methods: Data from AAV patients with PFTs performed between 2008 and 2018 were extracted retrospectively from the database of a tertiary vasculitis center. Demographic and disease characteristics, imaging data and follow-up results were assessed and compared to PFT results. Results: The final analysis encompassed 147 patients. The mean time between first PFT and follow-up was 7.0 ± 11.0 months. In Granulomatosis with Polyangiitis (GPA), forced expiratory vital capacity (FVCex, p<0.001), residual volume (RV, p<0.001) and the diffusion capacity of carbon oxide (TLCO, p=0.003) were significantly reduced compared to the reference value of 100% predicted. There was no significant difference between patients with or without pulmonary manifestations. In Microscopic Polyangiitis (MPA), reductions of FVCex (p<0.001), TLC (p=0.005), and TLCO (p=0.003) were observed. In Eosinophilic Granulomatosis with Polyangiitis (EGPA), total airway resistance (RAWtot, p=0.024) and RV (p=0.009) were significantly elevated and TLCO was reduced (p=0.014). Interstitial lung disease (ILD) is associated with a decline of FVCex (-15.7%, p=0.0028), TLC (-26.5%, p<0.001), RV (-38.9%, p=0.023) and TLCO (-29.1%, p=0.007). Significant differences were neither detected between first PFT and follow-up examination, nor between patients with active versus inactive disease. Conclusions: AAV patients presented with characteristic alterations in PFTs according to their respective pulmonary and/or airway manifestations. These results did not change over time and were independent from vasculitis activity.
Gesehen am 22.10.2024